2003
DOI: 10.1080/10473289.2003.10466134
|View full text |Cite
|
Sign up to set email alerts
|

Daily Surface UV Exposure and Its Relationship to Surface Pollutant Measurements

Abstract: For the past 30 years, the stratospheric ozone layer has decreased in the Northern Hemisphere. The main effect of this ozone decrease was an expected increase in the UV radiation at the Earth's surface, but there has been no clear evidence of an increasing urban trend in surface UV. This study shows that specific air pollutants can reduce the increased surface levels of UV radiation and offers an explanation for why the expected surface UV increases have not been observed, especially in urban regions.A U.S. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…It was found that DDR has little dependence on realistic values of TOC. In clear-sky periods, variations of tropospheric ozone do little to influence UV radiation, including its scattering, when compared to stratospheric ozone [Barnard et al, 2003]. Figure 3 shows that the sensitivity of DDR to w increased from AOD = 0.05 to AOD = 1.00, and this was also found to occur for g and ga. A further test was conducted to see how much a change in DDR of 0.02 would affect the retrieval of w as AOD is varied.…”
Section: Sensitivity/error Analysismentioning
confidence: 56%
“…It was found that DDR has little dependence on realistic values of TOC. In clear-sky periods, variations of tropospheric ozone do little to influence UV radiation, including its scattering, when compared to stratospheric ozone [Barnard et al, 2003]. Figure 3 shows that the sensitivity of DDR to w increased from AOD = 0.05 to AOD = 1.00, and this was also found to occur for g and ga. A further test was conducted to see how much a change in DDR of 0.02 would affect the retrieval of w as AOD is varied.…”
Section: Sensitivity/error Analysismentioning
confidence: 56%
“…This wavelength dependence of OMI-Brewer bias for moderatehigh aerosol load may be partially attributed to the aerosol influence over the OMUVB products. Aerosols can also increase effective absorption path for tropospheric ozone and other anthropogenic gases causing more effective UV reduction at shorter UV wavelengths (Bernard et al, 2003;Kaskaoutis et al, 2006;Badarinath et al, 2007).…”
Section: Data Set 4: Cloud-free Conditions With Moderate-high Aerosolmentioning
confidence: 99%
“…The API is a simple and generalized way to describe air quality, with a higher API corresponding to more serious air pollution. Some studies have shown that air pollution can reduce the surface levels of UV irradiance [39]. For both measuring days, (i) the mean API was approximately 62, (ii) the result of the diurnal variations of the ambient UVR irradiance were bell-shaped curves with peaks at approximately noon (approximately 12:00 CST, SEA 82°), and (iii) the ambient UVR irradiances were nearly the same for the two days.…”
Section: Discussionmentioning
confidence: 89%